Effect of Ag addition into the Activity of Titanium Silicate-1 Catalyst in Cyclohexanone Reaction - Dyah Fitasari; Didik Prasetyoko; Suprapto Suprapto (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
Titanium Silicate-1 (TS-1) has been successfully modified by combining Silver (Ag) metals. In this study, the preparation of Ag/TS-1 was carried out by impregnation method using a solution of silver nitrate (AgNO3) as a precursor to TS-1 with a loading variation of 0.5%, 1%, 2%, and 4%. Impregnation carried out on TS-1 aims to disperse Ag (1) only attached to the surface of TS-1 particles (before calcination/TK) and (2) on the entire surface of TS-1 particles (after calcination/K). The synthesized catalyst was then characterized by X-ray diffraction, infrared spectroscopy, and pyridine adsorption techniques. The XRD pattern shows that all the catalysts have high crystallinity with MFI structure, and there is no other crystalline phase. The infrared spectra showed that the titanium tetrahedral in TS-1 remained after Ag impregnation. The TS-1 and Ag/TS-1 catalysts were analyzed for their surface acidity using pyridine adsorption on the sample. The pyridine adsorption technique showed the presence of Lewis sites on Ag/TS-1. In this study, the presence of Ag loading on the Ag/TS-1 catalyst affected the TS-1 catalytic activity. The amount of cyclohexanone oxime product produced in XAg/TS-1 was more than in Ag/TS-1.